2005
DOI: 10.1152/ajplung.00103.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of veins in regulation of pulmonary circulation

Abstract: Pulmonary veins have been seen primarily as conduit vessels; however, over the past two decades, a large amount of evidence has accumulated to indicate that pulmonary veins can exhibit substantial vasoactivity. In this review, the role of veins in regulation of the pulmonary circulation, particularly during the perinatal period and under certain pathophysiological conditions, is discussed. In the fetus, pulmonary veins contribute a significant fraction to total pulmonary vascular resistance. At birth, the vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
94
1
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 156 publications
(219 reference statements)
7
94
1
5
Order By: Relevance
“…This was demonstrated in the present study with endothelin-1, and in related studies using lung explants for histamine and serotonin [20,21]. In all these studies, pulmonary veins responded more strongly than pulmonary arteries, corroborating many other findings in rat, sheep and human lungs [29].…”
Section: Discussionsupporting
confidence: 92%
“…This was demonstrated in the present study with endothelin-1, and in related studies using lung explants for histamine and serotonin [20,21]. In all these studies, pulmonary veins responded more strongly than pulmonary arteries, corroborating many other findings in rat, sheep and human lungs [29].…”
Section: Discussionsupporting
confidence: 92%
“…Arrigoni and colleagues (1) observed that the relaxation in response to acetylcholine, which also occurs by release of nitric oxide from the endothelium, was greater in 14-day-old porcine pulmonary veins compared with fetal veins. Similarly, Gao and Raj (9) found that acetylcholine is 10-fold more potent in relaxing pulmonary veins of newborn than fetal lambs. The postnatal increase in relaxation response we observed may thus be due to an increase in available nitric oxide from the endothelium after birth (2) as well as the increase in ET-B receptor density previously described (16,23).…”
Section: Discussionmentioning
confidence: 83%
“…We have previously shown that a 30-min exposure to 100% O 2 significantly increases fifth-generation pulmonary arterial contractility in vitro to norepinephrine and potassium chloride compared with 21% O 2 (14). We speculate that we could not replicate this finding in vivo because of a) use of a different vasoconstrictor agent (thromboxane analog, U46619 instead of norepinephrine and potassium chloride); b) a higher degree of biologic variability in the intact lamb model, including the complex contribution of pulmonary arteries, arterioles and veins to PVR in the intact lung and lamb (23); and c) measurement at different points in time (24 h in our previous study versus 2-3 h in the current study). For instance, it is possible that a change in gene expression may require a longer interval to manifest as increased contractility.…”
Section: Discussionmentioning
confidence: 83%